Challenges to German Idealism - Goudeli, K. author. aut Link
XII, 218 p.
Keywords: This book offers an important reappraisal of Schelling's philosophy and his relationship to German Idealism. Focusing on Schelling's self-critique in early identity philosophy the author rejects those criticisms of Schelling made by both Hegel and Heidegger. This work significantly redraws the boundaries of metaphysical thinking, arguing for a dialogue between rational philosophy, mythology and cosmology.